Characteristics of Self‐Reported Sleep and the Risk of Falls and Fractures: The Women's Health Initiative (WHI). (21st November 2018) - Cauley, Jane A; Hovey, Kathleen M; Stone, Katie L; Andrews, Chris A; Barbour, Kamil E; Hale, Lauren; Jackson, Rebecca D; Johnson, Karen C; LeBlanc, Erin S; Li, Wenjun; Zaslavsky, Oleg; Ochs‐Balcom, Heather; et al.
ABSTRACT: Sleep disturbances are common and may influence falls and fracture directly by influencing bone turnover and muscle strength or indirectly through high comorbidity or poor physical function. To investigate the association between self‐reported sleep and falls and fractures, we prospectively studied 157, 306 women in the Women's Health Initiative (WHI) using information on sleep quality, sleep duration, and insomnia from questionnaires. Annual self‐report of falling two or more times (ie, "recurrent falling") during each year of follow‐up was modeled with repeated measures logistic regression models fit by generalized estimating equations. Cox proportional hazards models were used to investigate sleep disturbance and time to first fracture. We examined the risks of recurrent falls and fracture by sleep duration with 7 hours as referent. We examined the risks across categories of sleep disturbance, insomnia status, and sleep quality. The average follow‐up time was 7.6 years for falls and 12.0 years for fractures. In multivariable adjusted models, including adjustment for comorbidity, medications, and physical function, women who were short (≤5 hours) and long (≥10 hours) sleepers had increased odds of recurrent falls (odds ratio [OR] 1.28; 95% confidence interval [CI], 1.23 to 1.34 and OR 1.25; 95% CI, 1.09 to 1.43, respectively). Poor sleep quality, insomnia, and more sleep disturbances were also associated with an increased odds of recurrent falls. Short sleep was associated with an increased risk of all fractures, and upper limb, lower limb, and central body fractures, but not hip fractures, with hazard ratios ranging from 1.10 to 1.13 ( p  < 0.05). There was little association between other sleep characteristics and fracture. In conclusion, short and long sleep duration and poor sleep quality were independently associated with increased odds of recurrent falls. Short sleep was associated with modest increase in fractures. Future long‐term trials of sleep interventions should include falls and fractures as endpoints. © 2018 American Society for Bone and Mineral Research.